A high‐performance FPGA‐based BWA‐MEM DNA sequence alignment. (7th May 2019) - Pham‐Quoc, Cuong; Kieu‐Do, Binh; Thinh, Tran Ngoc
Summary: Over the last decades, Bioinformatics has been being in its honeymoon phase with more and more new algorithms as well as their improvements proposed. In Bioinformatics, the sequence alignment step is considered as an integral part that directly contributes to the DNA, RNA, or protein identifications. Despite the undeniable enhancements from the provided algorithms and computing architectures in the recent years, it is still far more to state that sequence alignment has already achieved the ideal performance. In this work, we focus on one of the most perfect justifiable steps in a state‐of‐the‐art DNA/RNA alignment algorithm, the seed extension step in the BWA‐MEM algorithm. We propose a high‐speed and less power consumption FPGA‐based IP core that is designed in a pipeline model under various FPGA technologies. Our core is able to operate at more than 200 MHz in almost all FPGA architectures and even up to 529 MHz on a Xilinx Virtex 6 FPGA device. The core can provide speed‐ups by up to 350× when compared with an Intel Core i5 general purpose processor.